360 Video Trend on YouTube Before and During the COVID-19 Pandemic. (March 2022) - Martínez, Víctor Cerdán; García, Alberto Luis García; Moraleda, Ignacio José Martín
In 2015, YouTube was the first online platform to enable the option of uploading and playing 360-degree videos on the Internet. In 2020, during the COVID-19 pandemic, the consumption of these videos rebounded. To conclude this, we performed a quantitative analysis with the data from searches for '360 video' on YouTube from the four countries most affected by COVID-19 during the first months of the pandemic: the USA, the UK, Spain and Italy. Even though the analysis of variance (ANOVA), according to Fisher's F (0.48 < 2.62), shows there is a correlation between searches in the USA, the UK, Spain and Italy for the past 10 years, the tendency changes when the first months of the pandemic are analysed. We conclude that each country's restrictions, by which citizens were forced to stay at home during different dates, depending on the country, may have influenced the consumption of 360-degree videos on YouTube.